2001
DOI: 10.1093/treephys/21.8.489
|View full text |Cite
|
Sign up to set email alerts
|

Decline in stomatal response to leaf water deficit in Corylus maxima cuttings

Abstract: Many woody species can be propagated from leafy cuttings. However, following rooting, cuttings of Corylus maxima Mill. cv. Purpurea do not always survive the transition from a highly supportive rooting environment (e.g., fog) to a more natural environment where evaporative demand is higher. We found that it is not the supply of water to leaves, but stomatal dysfunction that leads to severe water deficits in the rooted cuttings. Two hours after well-rooted cuttings were transferred from the rooting environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Measurements of stomatal pore dimensions indicated more rounded stomatal pores in cuttings of C. maxima than in intact plants. Qualitatively, scanning electron microscopy has also shown this phenomenon in cuttings of C. maxima (Fordham et al 2001). Similarly, the development of stomata in vitro leads to progressively more rounded stomatal pores than the elliptical pores observed in ex vitro stomata (Ziv et al 1987, Santamaria et al 1993, Zacchini et al 1997, and is associated with irregular stomatal function (Marin et al 1988).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Measurements of stomatal pore dimensions indicated more rounded stomatal pores in cuttings of C. maxima than in intact plants. Qualitatively, scanning electron microscopy has also shown this phenomenon in cuttings of C. maxima (Fordham et al 2001). Similarly, the development of stomata in vitro leads to progressively more rounded stomatal pores than the elliptical pores observed in ex vitro stomata (Ziv et al 1987, Santamaria et al 1993, Zacchini et al 1997, and is associated with irregular stomatal function (Marin et al 1988).…”
Section: Discussionmentioning
confidence: 94%
“…It has been extensively reported that stomata developing during in vitro micropropagation, under very high humidity and low VPD, have a reduced capacity to control water loss in response to desiccation. In C. maxima , we have shown that similar stomatal dysfunction can also occur during the propagation of leafy cuttings (Fordham et al 2001). The present study investigated effects on stomatal sensitivity to other stimuli, and whether it is severance from the stock‐plant or the extremely supportive rooting environment that leads to stomatal dysfunction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In all the mentioned studies, the short-term response of the stomata to VPD was investigated, and the focus was on the stomatal response to high VPD. However, when plants were grown at low VPD, the behaviour of the stomata in response to desiccation or ABA changed and the stomata showed a diminished response to closing stimuli ( Fordham et al ., 2001a, b ; Rezaei Nejad and van Meeteren, 2005 , 2007 , 2008 ; Rezaei Nejad et al , 2006 ; Fanourakis et al , 2011 ; Arve et al , 2012 ; Aliniaeifard and van Meeteren, 2013 ; Aliniaeifard et al , 2014 ). Even when full-grown leaves were transferred from high to low VPD this loss of stomatal response to closing stimuli could be induced ( Rezaei Nejad and van Meeteren, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The problem is thought to be due to the high RH in the culture containers, but it is also clearly affected by the cytokinins in the culture medium (Santamaria et al 1993). Furthermore, a failure of stomata to close properly in response to desiccation or ABA has been shown in rooted leafy cuttings after transferring from the humid conditions of the propagator to one of increased evaporative demand (Fordham et al 2001a, Fordham et al 2001b).…”
Section: Introductionmentioning
confidence: 99%